Prosopographical method in the study of regional elites (based on the materials of the cossack officials of the Lubny cossack regiment of the mid-17th - second half of the 18th century) - Барсуков, Олександр (ВПЦ "Київський університет", 2025)
Background. The use of prosopography has become an important area of historical research, especially in the context of studying elites and social groups. Having originated in the nineteenth century, this method finally took shape as a separate discipline in the twentieth century, thanks to Lawrence Stone, who defined it as a tool for studying career trajectories, social connections, and economic activities of representatives of specificgroups. The article analyses the application of the prosopography method to the study of the Cossack officers of the Lubny Regiment, and considersthe role of the source base and historiography in the study of regional elites.Methods. The study is based on the prosopographical method, which was used to create a questionnaire to analyse the career trajectories, social relations and economic activities of representatives of the Cossack officers of the Lubny Regiment, and the study also uses a chronological approach and the principle of historicism in analysing the historiography and source base of the issue.Results. As a result of the study, the stages of formation of the prosopographic method in Ukrainian historiography are outlined and a corpus of sources is collected, which allows studying the Cossack elite of the Lubny Regiment in its regional and national contexts. The study also proposes a questionnaire structure that allows us to identify career trajectories, social connections, economic activity, and the degree of political influence of the regimental officers.Conclusions. On the basis of the analysis of historiography, sources and prosopographic questionnaires, the article identifies thepossibilities of using the prosopographic method to study regional elites, in particular, the sergeant major of the Lubny regiment in the structure of the Hetmanate.

Вступ. Застосування методу просопографії стало важливим напрямом в історичних дослідженнях, особливо у контексті вивчення еліт і соціальних груп. Зародившись у XIX ст., цей метод остаточно оформився як окрема дисципліна у XX ст. завдяки Лоренсу Стоуну, який визначив його як інструмент для вивчення кар'єрних траєкторій, соціальних зв'язків та економічної діяльності представників конкретних груп. У пропонованій статті проаналізовано застосування методу просопографії до вивчення козацької старшини Лубенського полку, а також розглянуто роль джерельної бази й історіографії в дослідженні регіональних еліт.Методи . В основу дослідження покладено просопографічний метод, за допомогою якого створено анкету для аналізу кар'єрних траєкторій, соціальних зв'язків та економічної діяльності представників козацької старшини Лубенського полку. Також у дослідженні застосовано хронологічний підхід і принцип історизму під час аналізу історіографії та джерельної бази питання.Результати. Унаслідок дослідження окреслено етапи становлення просопографічного методу в українській історіографії та зібрано корпус джерел, що сприяє вивченню козацької еліти Лубенського полку в її регіональному і загальнодержавному контекстах. У статті також запропоновано структуру анкети, що дає змогу виявити кар'єрні траєкторії, соціальні зв'язки, економічну активність і рівень політичного впливу представників полкової старшини.Висновки. На основі аналізу історіографії, джерел і просопографічних анкет визначено можливості застосування просопографічного методу для дослідження регіональних еліт, зокрема старшини Лубенського полку в структурі Гетьманщини.
Просопографічний метод в дослідженнях регіональних еліт (на матеріалах козацької старшини Лубенського полку середини XVII – другої половини XVIII ст.)
Keywords: Cossack Hetmanate; Cossack Officials; Lubny Cossack regiment; prosopography; elite; historical sources; social history; Cossack Hetmanate; Cossack Officials; Lubny Cossack regiment; prosopography; elite; historical sources; social history; Гетьманщина; козацька старшина; Лубенський полк; просопографія; еліта; історичні джерела; соціальні історія; Лубенський полк; просопографія; еліта; історичні джерела; соціальні історія